Protein profiles of field isolates ofBacillus anthracis from different endemic areas of Indonesia - Poerwadikarta, M Bhakti (Indonesian Journal of Animal and Veterinary Sciences, 1998)
Sonicated cell-free extract proteins of 14 field isolates ofBacillus anthracis from six different endemic areas of Indonesia were analyzed by the use of sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) methods . The protein profiles of each field isolate tested demonstrated slightly different at the protein bands with molecular weights of 18, 37, 52, 65 and 70 kDa, and varied between the field isolates and vaccine strains. The variation could provide clues to the source of anthrax transmission whether it was originated from similar strain or not. Â  Key words : Protein profiles, Bacillus anthracis, SDS-PAGE